2005
DOI: 10.1093/ajcn/81.1.230s
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and bioefficacy of polyphenols in humans. I. Review of 97 bioavailability studies

Abstract: Polyphenols are abundant micronutrients in our diet, and evidence for their role in the prevention of degenerative diseases is emerging. Bioavailability differs greatly from one polyphenol to another, so that the most abundant polyphenols in our diet are not necessarily those leading to the highest concentrations of active metabolites in target tissues. Mean values for the maximal plasma concentration, the time to reach the maximal plasma concentration, the area under the plasma concentration-time curve, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

92
2,699
11
71

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 3,595 publications
(2,957 citation statements)
references
References 140 publications
92
2,699
11
71
Order By: Relevance
“…Among the dietary antioxidants, the phenolic compounds, secondary metabolites occurring in plants, are the most abundant natural antioxidants [30]. They protect plants against harmful environmental conditions and are divided in two main categories, namely, flavonoids and nonflavonoids [31]. The significant correlation between the total polyphenol content and flavonoids content, as observed in this study, was also reported in other studies, in grape pomace extracts [32] and buckwheat extracts [33].…”
Section: Discussionsupporting
confidence: 87%
“…Among the dietary antioxidants, the phenolic compounds, secondary metabolites occurring in plants, are the most abundant natural antioxidants [30]. They protect plants against harmful environmental conditions and are divided in two main categories, namely, flavonoids and nonflavonoids [31]. The significant correlation between the total polyphenol content and flavonoids content, as observed in this study, was also reported in other studies, in grape pomace extracts [32] and buckwheat extracts [33].…”
Section: Discussionsupporting
confidence: 87%
“…It is also known that absorbed, low molecular weight phenolics, such as orcinol and quinol, can contribute to the digestible energy content of the diet without necessarily contributing to its nutritional value (Iason and Murray, 1996). Although it has been reported that dietary flavonoids (quercetin, genistein, catechin) are absorbed by humans (Paganga and Rice-Evans, 1997;Day et al, 2001;Manach et al, 2005), no phenolic compounds or any of the above metabolites could be detected, in our study, in the liver or plasma from lambs fed the grass diet. Three possible explanations may be offered to explain these findings.…”
Section: Discussioncontrasting
confidence: 66%
“…Since only flavonol monomers and dimeric proanthocyanidins are absorbed [58][59][60][61], systemic effects of proanthocyanidins would be limited to these compounds or eventually to not yet characterized metabolites and/or colonic degradation products from the polymeric molecules [58]. In this context, our findings cannot help to rationalize the cardiovascular protection nor provide a molecular interpretation for the anti-inflammatory effects of pistachio nut diets [20].…”
Section: Conclusive Remarksmentioning
confidence: 87%